El bien como objeto del querer. Suárez y los presupuestos apetitivos y cognoscitivos de la acción racional - Alejandro G. Vigo (Scientia et Fides, 2017)
The good as the object of wanting. Suárez on the appetitive and cognitive conditions of rational action This paper discusses Suárez’s characterization of the formal object of wanting, i.e. the good. Wanting, in all its possible forms, is based on cognition, in its various possible forms. But the starting point for wanting something is given in a judgement about its goodness. What is wanted, in its turn, provides the starting point for deliberation. The ratio boni marks the first transtion (i.e. the transtition from cognition to wanting), the ratio finis the second one (i.e. the transition from wanting to deliberation).